Ethnic diversity and local governance quality The case of Opole Province in Poland - Opiola, Wojciech (Studies in Politics, Security and Society, 2020)
The book is devoted to relations between the ethnic diversity and the quality of governance at the local level. Opolskie province in Poland is a case for explaining this interdependence. That is because of its history of multiculturalism and the present state of its ethnic diversity. The important feature of this region is, that nearly half of the communes is ethnically homogenous when the rest is ethnically diversified with a strong position of German and Silesian minorities. The preliminary assumption was, that the quality of governance would be higher in communes characterized by ethnic diversity. On the basis of the nested analysis method, authors conducted quantitative and qualitative analysis.